Navigating the Post-Pandemic Landscape: Challenges and Strategies of a Beverage Company - Boon Keong Teow; Rashmi Chaudhary; Nur Syafarina Binti Ani; Nur Izzatul Syazirah Binti Mohamed Nizam; Nur Qisha Atierah Binti Faridzail; Nur Safirah Binti Mohd Safari; Priyanshu Mittal; Daisy Mui Hung Kee (AIBPM Publisher, 2024)
This study explores Coca-Cola's adaptive responses to challenges presented by the COVID-19 pandemic, with a focus on how targeted training programs can enhance resilience and drive innovation in areas such as supply chain management, marketing strategies, and employee adaptation. Using a mixed-method approach, the research gathered quantitative and qualitative data through Google Forms surveys and focus groups with Coca-Cola employees in Malaysia. Results highlight that supply chain disruptions and shifting consumer demands were significant obstacles, while an increased focus on employee well-being and digital transformation provided notable opportunities. Findings reveal that Coca-Cola's